(untitled) (Reflection and Critique Law Magazine, 2020)
The present study aims to analyze the effects of the legislative modification brought by Law 13,467/17,among other reforms, drastically modified the provisions of collective labor law. For decades, the trade unions of the categories were responsible for negotiating the rules between the employee and employer, within labor standards. With the reform of the Law, union work lost strength and notoriety, being placed in a position of mere supporting role in labor relations. It is concluded, certain that it is important to analyze the problem involving the possibility of the labor norm being in retrogression as to collective rights. For the construction of this work, books, periodicals, scientific articles from renowned websites and other materials were used.